Gambaran pengetahuan dan sikap dokter gigi di indonesia mengenai OPMD (Laporan Penelitian) - Echita Mulia Saputri; Firstine Kelsi Hartanto (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Oral cancer is one of the most causes of morbidity and mortality due to malignancy in Indonesia. This problem usually occurs because the cancer is found late in its development. Oral Potentially Malignant Disorders (OPMD) can be detected and treated as early as possible to prevent their transformation into oral cancer by dentists with a good knowledge and attitude about OPMD. Aim: To describe the knowledge and attitudes of dentists in Indonesia regarding OPMD. Method: Descriptive observational study with a cross-sectional design using an online questionnaire (google form) consisting of 47 questions about knowledge and attitude to 167 dentists in Indonesia. The knowledge was categorized into high, moderate, and low levels. The attitude was categorized into good, moderate, and low levels. Results: This study collects data from 167 people according to the inclusion criteria, consisting of 124 women and 43 men, of whom were aged 20-29 years (58 people), 30-49 years (97 people), and >50 years (12 people). A total of 121 respondents have a high level of knowledge and 46 respondents in the moderate category meanwhile, 124 respondents have good attitude categories, 42 respondents in the moderate categories, and one respondent in the low one. Conclusion: The dentist in Indonesia has a high level of knowledge with an average score of 18.86+0.23 and a good level of attitude with an average score of 15+0.18.